Three new species of the genus Nudina Staudinger, 1887 from northern Indochina (Lepidoptera: Erebidae: Arctiinae: Lithosiini) - Volynkin, Anton V.; Huang, Si-Yao; Spitsyna, Elizaveta A.; Bolotov, Ivan N.; Spitsyn, Vitaly M. (Zootaxa, 2021)
Three new species of the genus Nudina Staudinger, 1887 are described from northern Indochina: N. ankistro Volynkin, Huang, Bolotov & Spitsyn, sp. nov. (Northern Myanmar), N. harpago Volynkin & Huang, sp. nov. (Northern Vietnam) and N. witti Spitsyn, Volynkin, Huang & Bolotov, sp. nov. (Northern Vietnam and Northern Myanmar). The new species represent a separated species-group which is established and characterized.